2018
DOI: 10.1080/02656736.2018.1502896
|View full text |Cite
|
Sign up to set email alerts
|

Innate/inflammatory bioregulation and clinical effectiveness of whole-body hyperthermia (balneotherapy) in elderly patients with osteoarthritis

Abstract: Objectives: Balneotherapy with mud application (mud therapy) is a common hydrothermal intervention for the treatment and rehabilitation of elderly patients with osteoarthritis, leading to anti-inflammatory effects. The main purpose of this investigation was to study a role for regulatory T cells in these anti-inflammatory effects. The second objective was to assess whether the neutrophil-mediated innate response is affected by these anti-inflammatory effects. Methods: Thirty-six elderly patients with knee oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…The results showed that mud therapy significantly improved osteoarthritis-related pain, stiffness, and physical function. It also increased knee flexion and extension angle [11]. Balneotherapy has short-and long-term effects on patients with low back pain-another noninflammatory musculoskeletal disease.…”
Section: Therapeutic Properties Of Natural Medicinal Resourcesmentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed that mud therapy significantly improved osteoarthritis-related pain, stiffness, and physical function. It also increased knee flexion and extension angle [11]. Balneotherapy has short-and long-term effects on patients with low back pain-another noninflammatory musculoskeletal disease.…”
Section: Therapeutic Properties Of Natural Medicinal Resourcesmentioning
confidence: 94%
“…Osteoarthritis is a degenerative musculoskeletal disease and leading cause of pain, disability, and impaired quality of life [4,10,11]. It affects synovial joints (mainly hips and knees), in which cartilage destruction, subchondral bone remodeling, osteophyte formation, and synovial inflammation are found, thereby leading to joint stiffness [11]. Osteoarthritis usually affects approximately 10% of people over 60 years of age [10].…”
Section: Therapeutic Properties Of Natural Medicinal Resourcesmentioning
confidence: 99%
“…In a psoriasis-like murine model, balneotherapy suppressed lesional IL-23 and IL-17A, cytokines involved in maintaining chronic inflammation (Lee et al 2014). C-reactive protein levels, which rise in response to inflammation, decrease significantly after balneotherapy (Gálvez et al 2018a(Gálvez et al , 2018b.…”
Section: Dear Editormentioning
confidence: 99%
“…Rinaldi et al (2006) demonstrated in vitro that sulphurous mineral water favours the short-term survival of neutrophils, speeding up the resolution of infections and preventing further inflammation. Studies conducted in patients with osteoarthritis who underwent hydrotherapy or mud-bath therapy showed that, after the treatment, neutrophils' circulating and functional capacity increased, reflecting a greater defence capacity against pathogens and thus a potential lower susceptibility to infections (Gálvez et al , 2018a(Gálvez et al , 2018b. Balneotherapy may also contribute to increase cortisol levels in healthy and subhealthy people.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation